A Comparison between Nasal Intermittent Positive Pressure Ventilation and Nasal Continuous Positive Airway Pressure Ventilation in the Treatment of Neonatal Respiratory Distress Syndrome - Ahmad Shah Farhat; Ashraf Mohammadzadeh; Reza Saeidi; Shadi Noorizadeh (Mashhad University of Medical Sciences, 2015)
Background: Nasal intermittent positive pressure ventilation (NIPPV) is a non-invasive ventilatory mode, which delivers mechanical ventilation via nasal tubes or prongs. The present study was conducted to compare the efficacy of NIPPV and nasal continuous positive airway pressure ventilation (NCPAP) in reducing the need for intubation in preterm infants with respiratory distress syndrome (RDS). Methods: This randomized, clinical trial was conducted at the neonatal intensive care unit of Imam Reza Hospital, affiliated to Mashhad University of Medical Sciences during eight months since April 2014. Preterm infants with RDS were recruited before showing any indications for endotracheal intubation after birth. The NIPPV and NCPAPV groups were matched in terms of clinical characteristics. Each infant was randomized to receive either NIPPV or NCPAPV immediately after extubation. Nasal ventilation was deemed successful if intubation was not required within at least 72 hours. Brain sonography was carried out on the third day of life in all infants. Data were recorded for all neonates until hospital discharge. Results: In total, 28% (15/53) and 26.4% (14/53) of infants in the NIPPV and NCPAPV groups were intubated within the first 72 h after birth, respectively (P=0.168). Neither of the procedures induced major adverse effects, although the incidence rate and severity of intraventricular hemorrhage were higher in the NIPPV group, compared to the NCPAPV group (P=0.026). Conclusion: Although NIPPV is confirmed as the first-line treatment for the management of neonatal RDS, this mode of ventilation showed no superiority over NCPAPV in eliminating the need for mechanical ventilation in the present study.